Efeito da tosquia estratégica no comportamento ingestivo de ovelhas Ile de France em pastagem de capim vaquero (Cynodon dactylon cv Vaquero) durante a estação de monta - Alves Cirne, Luis Gabriel; Silva Sobrinho, Americo Garcia da [UNESP]; Santana, Valeria Teixeira [UNESP]; Endo, Viviane [UNESP]; Almeida, Fabiana Alves de [UNESP]; Franco, Mariana Rezende [UNESP]; Silva, Felipi Ulian [UNESP]; Oliveira, Emanuel Almeida de [UNESP]; Pinto de Carvalho, Gleidson Giordano; Zeola, Nivea Maria Brancacci Lopes [UNESP] (Univ Estadual Londrina, 2014)
The experiment evaluated the effects of strategic shearing on feeding behavior in Ile de France ewes in Bermudagrass (Cynodon dactylon) grazing during breeding season. A total of 20 ewes, female, Ile de France breed, 4 years old, 71.10 kg of body weight, in grazing, in a completely randomized design with two treatments and ten repetitions, in which the treatments were composed by shorn and non-shorn animals. The length of the breeding season was 90 days, where the evaluations occurred in the 86th, 87th and 88th day of the experimental period. The grazing time (6.50 hours), rumination (1.59 hours) and idle (3.97 hours) have not changed (P> 0.05) by strategic shearing of the animals, as well as the frequency and the time by frequency grazing (18.33 grazing and 21.49 min/grazing), rumination (10.71 ruminations and 8.83 min/rumination) and idle (18.83 idles and 12.66 min/idle). In the same way, the number of bits per minute (26.37 bits) and the total daily bits (19.116 bits) of the animals were not affected. Thus, the strategic shearing in Ile de France ewes in Bermudagrass grazing during the breeding season does not alter animal feeding behavior.
Effect of strategic shearing on feeding behavior in Ile de France sheep in Bermudagrass (Cynodon dactylon cv Vaquero) grazing during breeding season
Keywords: Ethology; ewes; grazing